2006
DOI: 10.1007/s00442-006-0518-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of group size and pine defence chemicals on Diprionid sawfly survival against ant predation

Abstract: The defence chemicals and behavioural adaptations (gregariousness and active defensive behaviour) of pine sawfly larvae may be effective against ant predation. However, previous studies have tested their defences against very few species of ants, and few experiments have explored ant predation in nature. We studied how larval group size (groups of 5 and 20 in Neodiprion sertifer and 10, 20 and 40 in Diprion pini) and variation in levels of defence chemicals in the host tree (Scots pine, Pinus sylvestris) affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Sawflies are phytophagous and the Diprionidae are defoliators of conifer trees (Pinaceae) with digestive systems adapted to that purpose. The diverticular pouches, which branch off the diprionid larval foregut, are used to store hostplant-derived terpenoids that are regurgitated in defensive behaviors against predators [21][22][23][24][25][26][27]. Like N. abietis, the diverticular pouches of N. sertifer larvae have been shown to be muscular sacs lined with an impervious layer of cuticle [21].…”
Section: Discussionmentioning
confidence: 99%
“…Sawflies are phytophagous and the Diprionidae are defoliators of conifer trees (Pinaceae) with digestive systems adapted to that purpose. The diverticular pouches, which branch off the diprionid larval foregut, are used to store hostplant-derived terpenoids that are regurgitated in defensive behaviors against predators [21][22][23][24][25][26][27]. Like N. abietis, the diverticular pouches of N. sertifer larvae have been shown to be muscular sacs lined with an impervious layer of cuticle [21].…”
Section: Discussionmentioning
confidence: 99%
“…Social aggregation is one of the strategies that provide protective and facilitation effects aiding the survival and development of larvae [25], and has arisen independently in diverse animal taxa [26][27][28][29][30]. The majority of insects have immature stages, and the aggregation behaviors of larvae have been reported in many lineages including true flies [24,[31][32][33], sawflies [34][35][36][37], and beetles [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of this Other study showed that Dermaptera of genus Dorus are efficient herbivorous predators in corn monoculture (see Cruz 1991). Additionally, Buschman et al (1977) Some studies have shown that the result of ant-plant interaction is dependent of the species of predatory ants involved interaction (Byk & Del-Claro, 2010;Calabuig et al, 2015) and of the strategies of herbivorous against predation (Bächtold & Alves-Silva, 2013;Carita et al, 2006;Styrsky & Eubanks, 2010). Nevertheless, little is known about the behavior between pairs (predator-prey) determining plant protection.…”
Section: Discussionmentioning
confidence: 99%